The Effect Climate Change and Household Consumption Expenditure Growth in African Countries: A Generalized Method of Moment (GMM) Approach (Global Business Management Review (GBMR), 2024)
The issue of climate change has gained attention in the international space for almost a decade with institution reviewing some of the tactics to reduce its surge effect on household. This study investigates the effect of climate change on household consumption expenditure using data set from fifty four (54) African countries span 2013 to 2022. This study seeks to employ the Generalized Method of Moment (GMM) and the result of the study indicates that there is a short run relationship. the coefficient lag value of household consumption expenditure at several lags are statistically significant and are best instruments to be included in the model. The coefficient Co2 emission has a positive and statistical significant effect on household consumption. Temperature economic globalization and social globalization have a negative but non significant effect on household consumption expenditure. Political globalization has a positive but non significant effect on household consumption expenditure in African countries.